Meningkatkan Kreativitas Anak Kelompok A Melalui Kegiatan Menggambar Bebas Di PAUD Abdi Ananda Tahun Pelajaran 2022/2023 - Titin Astuti; M. Arzani; Juandra Prisma Mahendra (Jurnal Pembelajaran dan Pendidikan Dasar, 2024)
This research aims to increase the creativity of group A children through free drawing activities at Abdi Ananda Preschool for the 2022/2023 academic year. The subjects of this research were Group A children at PaudAbdiAnanda with a total of 13 children, namely 9 boys and 4 girls. This research method uses Classroom Action Research (PTK), which is research carried out systematically on various actions carried out by researchers to improve learning conditions and carried out in two cycles, with each cycle containing planning, implementation, observation and reflection. The results of this research show that there is an increase in children's creativity through free drawing activities. In the pre-cycle classical completion only reached 30.7%, in cycle I children's creativity increased by 23.1% to 53.8%, and in cycle II children's creativity increased by 38.5%, to 92.3% . This shows that an increase in the percentage of children's creativity in the Developing According to Expectations (BSH) criteria with a percentage of 92.3% has been achieved in this research. This means that most children's creativity can be increased through free drawing activities in group A at Paud Abdi Ananda for the 2022/2023 academic year.